2015
DOI: 10.1128/mbio.00929-15
|View full text |Cite
|
Sign up to set email alerts
|

Genomics and Ecophysiology of Heterotrophic Nitrogen-Fixing Bacteria Isolated from Estuarine Surface Water

Abstract: The ability to reduce atmospheric nitrogen (N2) to ammonia, known as N2 fixation, is a widely distributed trait among prokaryotes that accounts for an essential input of new N to a multitude of environments. Nitrogenase reductase gene (nifH) composition suggests that putative N2-fixing heterotrophic organisms are widespread in marine bacterioplankton, but their autecology and ecological significance are unknown. Here, we report genomic and ecophysiology data in relation to N2 fixation by three environmentally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
81
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(85 citation statements)
references
References 68 publications
(100 reference statements)
4
81
0
Order By: Relevance
“…2) but very little is known about their potential to fix N 2 (Dai et al ., ; Im Jeong et al ., ). The conserved nucleotide identity and synteny of the compared N 2 fixation gene clusters implies that this region was subject to lateral gene transfer, which has previously been reported for other heterotrophic diazotrophs (e.g., Cantera et al ., ; Bentzon‐Tilia et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…2) but very little is known about their potential to fix N 2 (Dai et al ., ; Im Jeong et al ., ). The conserved nucleotide identity and synteny of the compared N 2 fixation gene clusters implies that this region was subject to lateral gene transfer, which has previously been reported for other heterotrophic diazotrophs (e.g., Cantera et al ., ; Bentzon‐Tilia et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…Alternatively, their abundance and activity may fluctuate according to DOM dynamics. A pioneering genomics study targeting diazotrophic Alphaproteobacteria and Gammaproteobacteria isolated from coastal Denmark waters showed that these organisms devoted an important part of their genome to aromatic hydrocarbon metabolism, although diverse systems related to carbohydrate and fatty acid metabolism were also found [ Bentzon‐Tilia et al ., ], suggesting a flexible metabolism. Conversely, Severin et al .…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, when DIN concentrations were ≤0.09 μM we observed the highest rates of N 2 fixation (∼68 nmol L -1 d -1 ), associated with less diverse diazotroph communities (H′ = ∼1.5), typically dominated by Trichodesmium (at 30–50% of the diazotroph assemblage). In culture, cyanobacterial and proteobacterial diazotrophs have been shown to significantly decrease N 2 fixation with increasing DIN concentrations (Knapp et al, 2012; Bentzon-Tilia et al, 2015), indicating a switch to DIN supported growth (Kustka et al, 2003; Masuda et al, 2013; Bentzon-Tilia et al, 2015), which may reduce the demand for dissolved iron (Kustka et al, 2003). However, in the environment N 2 fixation is increasingly being found to occur outside of the classical ecological niche of low DIN waters (Fernandez et al, 2011; Knapp, 2012; Farnelid et al, 2013), and can even increase in response to simulated (mesocosm) and natural (mesoscale processes) co-additions of N with other nutrients (Dekaezemacker et al, 2013; Loscher et al, 2016).…”
Section: Discussionmentioning
confidence: 99%